FILMS FOR EFL: EXPLORING THE PERCEPTIONS OF A HIGH SCHOOL TEACHER - Sánchez, Estefanía; Férez, Pedro Antonio (Universitas Pendidikan Indonesia, 2021)
Research on teacher perceptions on the use of films in the secondary school English classroom is scarce since most studies have focused on other educational levels and on the opinions of students. Besides, most of these studies are merely of a theoretical nature. Consequently, there is a need for empirical research which sheds further light on both Compulsory Secondary Education and teacher perceptions on this matter. This study explores the perception of a secondary school teacher on the use of a film as a tool for conducting EFL classes. Data were obtained according to the following steps. Firstly, the English instructor was interviewed regarding her views on the use of authentic audio-visual materials in the English classroom. Then, the teacher examined a film-based lesson plan which included the advantages of authentic audio-visual resources for EFL as defined by experts in the field. Finally, the teacher was interviewed again to trace changes in her perception. The results of the study show that, in the initial interview, the participant’s opinion was positive although her use of films as a didactic aid was vague and minimal. However, in the final interview, she reflected a more positive view and she was willing to include films and their multiple educational benefits into her lessons, advocating, therefore, a more holistic understanding of EFL. The contextually situated awareness elicited through the teacher’s own experience of the lesson plan made her question her own classroom practice. This led to the amplification of the teacher’s understanding of EFL, which, at the post-intervention stage, emerged not only as a linguistic endeavour but also as a platform from where to promote critical thinking, aesthetic sensitivity or awareness towards issues of social justice.